An Investigation into Implementing Movies to Promote Cultural Awareness in The Civilization Classroom The Case of First-Year LMD Students at The Department of English - Amar Thelidji University Laghouat - Boumediene, Amine; NOUIOUA, Amira Hiba (Faculty of Letters and Foreign Languages Department of English, 2019)
Due to globalization and the widespread of technology that made of the world a borderless nation, the need to raise EFL students' cultural awareness has become pivotal to ensure the continuation of cultural diversity on the one hand, and the ease of communication between people on another. Nevertheless, civilization being the module dedicated for such a purpose seems to be misemployed, hence calling for new methods in order to realize its cultural objectives. Therefore, this study aims to describe the role of movies in promoting students' cultural awareness in the civilization classroom, in addition to minor purposes as to verify the content of the civilization course and the methods used in teaching it. To attain the goals of this research, a case study was conducted with forty first-year LMD students and two teachers of civilization in the department of English at the University Amar Thelidji Laghouat. As for the tools used to collect data, the researcher relied on self-completion questionnaires for both teachers and students. Thus, the data collected was analyzed quantitatively and qualitatively. Consequently, the findings of this research indicated that the two poles of the teaching-learning process agreed that movies would bring significant changes to the civilization course as it would increase interest for the module as well as open the door for new cultural aspects to be included in the teaching procedure. Moreover, as far as the students are concerned, the civilization course resembles a history course to them due to its lack of cultural materials and its total focus on historical facts. Besides, the teacher informants also admitted their reliance on historical facts when teaching. Additionally, it was also concluded that the course does not help in any way to shape students' cultural awareness, due to the absence of creativity and variation of teaching tools.